Comparative genomic analysis of Staphylococcus aureus isolates associated with either bovine intramammary infections or human infections demonstrates the importance of restriction-modification systems in host adaptation. Issue 2 (18th February 2022) - Park, Soyoun; Jung, Dongyun; O'Brien, Bridget; Ruffini, Janina; Dussault, Forest; Dube-Duquette, Alexis; Demontier, Élodie; Lucier, Jean-François; Malouin, François; Dufour, Simon; Ronholm, Jennifer
Abstract : Staphylococcus aureus is a major etiological agent of clinical and subclinical bovine mastitis. The versatile and adaptative evolutionary strategies of this bacterium have challenged mastitis control and prevention globally, and the high incidence of S. aureus mastitis increases concerns about antimicrobial resistance (AMR) and zoonosis. This study aims to describe the evolutionary relationship between bovine intramammary infection (IMI)-associated S. aureus and human pathogenic S. aureus and further elucidate the specific genetic composition that leads to the emergence of successful bovine IMI-associated S. aureus lineages. We performed a phylogenomic analysis of 187  S . aureus isolates that originated from either dairy cattle or humans. Our results revealed that bovine IMI-associated S. aureus isolates showed distinct clades compared to human-originated S. aureus isolates. From a pan-genome analysis, 2070 core genes were identified. Host-specific genes and clonal complex (CC)-specific genes were also identified in bovine S. aureus isolates, mostly located in mobile genetic elements (MGEs). Additionally, the genome sequences of three apparent human-adapted isolates (two from CC97 and one from CC8), isolated from bovine mastitis samples, may provide an snapshot of the genomic characteristics in early host spillover events. Virulence and AMR genes were not conserved among bovine IMI-associated S. aureus isolates. Restriction-modification (R-M) genes in bovine IMI-associated S. aureus demonstrated that the Type I R-M system was lineage-specific and Type II R-M system was sequence type (ST)-specific. The distribution of exclusive, virulence, and AMR genes were closely correlated with the presence of R-M systems in S. aureus, suggesting that R-M systems may contribute to shaping clonal diversification by providing a genetic barrier to the horizontal gene transfer (HGT). Our findings indicate that the CC or ST lineage-specific R-M systems may limit genetic exchange between bovine-adapted S. aureus isolates from different lineages.